Techno‐economic analysis of a hydrogen pipeline infrastructure - Norberg, Johannes (Luleå tekniska universitet, Institutionen för teknikvetenskap och matematik, 2024)
With hydrogen playing a major role for reaching net zero emissions, the main challenge will be the integration of the energy carrier. This includes solutions for storage, production and transportation of the gas. Alternatives for hydrogen transportation could include either train, truck or boat. However, the current most economical and promising technology is pipeline transmission, especially in northern Sweden, with new green projects suchas H2 Green Steel and HYBRIT. They will create a market that needs a hydrogen infrastructure, which hydrogen pipelines could provide. This thesis will cover a techno-economic evaluation of hydrogen piping, involving material, compressor technology and pipeline dimensions. Hydrogen is briefy covered in its main production, applications and transportation options in the beginning of the thesis. This will ultimately converge into a in-depth analysis of hydrogen piping. This analysis includes alternatives for compressors, materials for pipes and main technical challenges. The gathered information concluded that hydrogen transport will most likely use either reciprocating or centrifugal compressors. Centrifugal compressors have the advantage of managing high gas flows, and the reciprocating compressors are mature and have a high capacity for pressure. For materials, embrittlement is the main challenge when transporting hydrogen gas, and standard ASME B31.12 provides current directions for hydrogen piping. A yield strength of 30% is required in the material, to compensate for hydrogen’s attributes. Generally the higher the strength of the material, the higher the risk of embrittlement and pipe damage. Careful selection has to be made in termsof micro structure, strength and coating to minimise leakage. To realise how hydrogen infrastructure could be constructed, three scenarios where created. These scenarios were based on assumptions and article values to best illustrate future hydrogen transportation. Main scenario settings include a pressure ratio of Pratio < 1.5, and length ...